Investigation of ethnomedicinal plants of Subarnachar in Noakhali, Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
Subarnachar is one of the traditional and promising upazilla in Noakhali district of Bangladesh. A survey of ethnomedicinal plants of the area was conducted from December 2009 to August 2011. The present study records 84 species under 75 genera in 47 families which is known to be used for the treatment of 34 diseases/illness. Field observations and discussion with local informants revealed that the ethnomedicinal plant species and traditional knowledge of the area is at great risk because of many threats including habitat destruction, agricultural advancement, and excessive collection of plants, industrialization and urbanization. It is very essential to document these plant use information before their disappearing. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17085 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):77-86, 2011